The Obesity Paradox in Emergency General Surgery Patients. Issue 5 (May 2022) - Maloney, Sean R.; Reinke, Caroline E.; Nimeri, Abdelrahman A.; Ayuso, Sullivan A.; Christmas, A. Britton; Hetherington, Timothy; Kowalkowski, Marc; Sing, Ronald F.; May, Addison K.; Ross, Samuel Wade
Background: Operative management of emergency general surgery (EGS) diagnoses involves a range of procedures which can carry high morbidity and mortality. Little is known about the impact of obesity on patient outcomes. The aim of this study was to examine the association between body mass index (BMI) >30 kg/m 2 and mortality for EGS patients. We hypothesized that obese patients would have increased mortality rates. Methods: A regional integrated health system EGS registry derived from The American Association for the Surgery of Trauma EGS ICD-9 codes was analyzed from January 2013 to October 2015. Patients were stratified into BMI categories based on WHO classifications. The primary outcome was 30-day mortality. Longer-term mortality with linkage to the Social Security Death Index was also examined. Univariate and multivariable analyses were performed. Results: A total of 60 604 encounters were identified and 7183 (11.9%) underwent operative intervention. Patient characteristics include 53% women, mean age 58.2 ± 18.7 years, 64.2% >BMI 30 kg/m 2, 30.2% with chronic obstructive pulmonary disease, 19% with congestive heart failure, and 31.1% with diabetes. The most common procedure was laparoscopic cholecystectomy (36.4%). Overall, 90-day mortality was 10.9%. In multivariable analysis, all classes of obesity were protective against mortality compared to normal BMI. Underweight patients had increased risk of inpatient (OR = 1.9, CI = 1.7-2.3), 30-day (OR = 1.9, CI = 1.7-2.1), 90-day (OR = 1.8, CI 1.6-2.0), 1-year (OR = 1.8, CI = 1.7-2.0), and 3-year mortality (OR = 1.7, CI = 1.6-1.9). Conclusions: When stratified by BMI, underweight EGS patients have the highest odds of death. Paradoxically, obesity appears protective against death, even when controlling for potentially confounding factors. Increased rates of nonoperative management in the obese population may impact these findings.